2017
DOI: 10.1063/1.4975193
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic dielectric function within time-dependent density functional theory—Real time evolution versus the Casida approach

Abstract: Linear optical properties can be calculated by solving the time-dependent density functional theory equations. Linearization of the equation of motion around the ground state orbitals results in the so-called Casida equation, which is formally very similar to the Bethe-Salpeter equation. Alternatively one can determine the spectral functions by applying an infinitely short electric field in time and then following the evolution of the electron orbitals and the evolution of the dipole moments. The long waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…75,77 The calculations are commonly performed by diagonalizing the Casida matrix directly or by solving the equivalent problem with different iterative subspace algorithms. [78][79][80][81] The real-time-propagation formulation of TDDFT (RT-TDDFT) 82,83 is a computationally efficient alternative to frequency-space approaches with favorable scaling with respect to system size, 84 and has the additional advantage of being also applicable to the non-linear regime. However, RT-TDDFT results are often limited to absorption spectra or to analyses of transition densities, apart from a few exceptions focusing on characterizing plasmonic [45][46][47]85 or other electronic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…75,77 The calculations are commonly performed by diagonalizing the Casida matrix directly or by solving the equivalent problem with different iterative subspace algorithms. [78][79][80][81] The real-time-propagation formulation of TDDFT (RT-TDDFT) 82,83 is a computationally efficient alternative to frequency-space approaches with favorable scaling with respect to system size, 84 and has the additional advantage of being also applicable to the non-linear regime. However, RT-TDDFT results are often limited to absorption spectra or to analyses of transition densities, apart from a few exceptions focusing on characterizing plasmonic [45][46][47]85 or other electronic excitations.…”
Section: Introductionmentioning
confidence: 99%
“…As extensively shown in the past, the former is particularly capable of dealing with bigger systems. 30…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent quantum calculations using time dependent density functional theory (TDDFT) [33][34][35][36] reveals a different scenario when the metal NP size shrinks to the nanometer or subnanometer length scales [37][38][39][40][41]. TDDFT is implemented in both the frequency domain (lr-TDDFT: [42][43][44][45][46][47][48] in terms of the Casida matrix expressed in the Kohn-Sham electron-hole space) and time domain (rt-TDDFT: [49][50][51][52][53] based on the time evolution of the occupied Kohn-Sham orbitals). It is reported that rt-TDDFT is more computationally efficient technique than lr-TDDFT due to the favorable scaling with respect to system size [54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%